2019
DOI: 10.1002/celc.201901253
|View full text |Cite
|
Sign up to set email alerts
|

Insights in the Study of the Oxygen Reduction Reaction in Direct Ethanol Fuel Cells using Hybrid Platinum‐Ceria Nanorods Electrocatalysts

Abstract: This work reports on the synthesis and characterization of hybrid electrocatalysts based on Pt nanoparticles and ceria nanorods (CeO 2 NR) supported on Vulcan XC-72 carbon black (Pt x (CeO 2 NR) y C z ) and evaluation of their electrocatalytic activity towards the oxygen reduction reaction (ORR), aiming the application of 4-electrons process in direct ethanol fuel cells (DEFCs). The hybrid electrocatalysts are characterized by X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Figure shows the TEM image of the Pt/C electrocatalyst, which reveals that Pt nanoparticles (NPs) are uniformly dispersed and the average particle size is about 7.9 nm. The crystalline structures of Pt NPs were examined using high‐resolution transmission electron microscopy (HRTEM), and lattice fringes with distances of 0.23, 0.20, 0.14, and 0.12 nm, corresponding to the (111), 27 (200), 28 (220), 29 and (311) 29 planes, respectively, were observed and are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the TEM image of the Pt/C electrocatalyst, which reveals that Pt nanoparticles (NPs) are uniformly dispersed and the average particle size is about 7.9 nm. The crystalline structures of Pt NPs were examined using high‐resolution transmission electron microscopy (HRTEM), and lattice fringes with distances of 0.23, 0.20, 0.14, and 0.12 nm, corresponding to the (111), 27 (200), 28 (220), 29 and (311) 29 planes, respectively, were observed and are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Pinheiro et al reported a hybrid electrocatalyst constructed by Pt nanoparticles and CeO 2 nanorods supported on carbon black for ORR with the aim of application in fuel cells. [ 70 ] As a result, the electrocatalyst shows an improved current and power density than the commercial Pt‐based electrocatalysts. Li et al obtained a similar result and attribute the enhanced performance to that the interaction between CeO 2 and Pt nanoparticles, which prevents surface Pt nanoparticles from aggregation.…”
Section: Ceo2‐based Electrocatalystmentioning
confidence: 99%